Deviation of geodesics, particle trajectories and the propagation of radiation in gravitational waves in Shapovalov type III wave spacetimes - Osetrin, Konstantin E. (Symmetry)
A class of exact (non-perturbative) models of strong gravitational waves based on Shapovalov type III spacetimes and Einstein's vacuum equations is obtained. Exact solutions are found for the trajectories of particles and radiation in a gravitational wave in privileged coordinate systems. Exact solutions are obtained for the equations of geodesic deviation and tidal acceleration of particles in a gravitational wave in privileged coordinate systems. An explicit analytical law of transition from a privileged coordinate system to a synchronous reference system associated with a freely falling observer with an explicit selection of time and spatial coordinates is obtained. An explicit form of the metric of a gravitational wave in a synchronous frame of reference is obtained. For a synchronous frame of reference, the trajectories of particles and radiation, the deviation of geodesics, and tidal accelerations in a gravitational wave are obtained. The presented methods and approaches are applicable both to Einstein's general theory of relativity and to modified theories of gravity.